Mindfulness training attenuates the increase in salivary cortisol concentration associated with competition in highly trained wheelchair-basketball players - MacDonald, L. A.; Minahan, C. L. (Journal of Sports Sciences, 2018)
This study determined the effect of 8 wk of mindfulness training (MT) on salivary cortisol (sCort) and rate of salivary Immunoglobulin-A (sIgA) secretion in wheelchair-basketball players during a competition period. The mindful group completed 8 weeks of MT in addition to training and competition. sCort and rate of sIgA secretion were measured at baseline, at 2-week intervals, the end and 2 weeks following the intervention. A significant time and group interaction was observed for sCort (F = 3.297, P = 0.040, ES = 0.191); sCort increased in the control group from MT-BL to MT-2wk (P = 0.001) and remained significantly elevated at MT-4wk (P = 0.013) and MT-6wk (P = 0.002). sCort decreased from MT-6wk to MT-8wk (P < 0.001) and concentrations were not different at MT-8wk and Post-2wk to MT-BL (P > 0.05). Mindful group sCort increased from MT-BL to MT-2wk (P = 0.042) but decreased to concentrations no different to MT-BL for the rest of the intervention period (P > 0.05). There were no group differences in rate of sIgA secretion during the intervention (P = 0.810). It was concluded that 8 weeks of MT attenuated the increase in sCort associated with the competition period.